Pelaksanaan Program Kelas Ibu Hamil di Puskesmas - Fithri Ratnasari; Irwanto Irwanto (Universitas Malahayati Lampung, 2023)
ABSTRACT Health development programs in Indonesia are still prioritized on efforts to improve the health status of mothers and children, especially those who are most vulnerable to health, namely pregnant women, giving birth and babies during the perinatal period. The success of maternal health programs can be assessed through the main indicators of the Maternal Mortality Rate (MMR). The Pregnant Women Class is a means to learn together about health for pregnant women, in the form of face-to-face in groups to increase the knowledge and skills of mothers regarding pregnancy, childbirth, and postpartum. The purpose of this study was to determine the implementation of classes for pregnant women in the UPTD Pasirkaliki Public Health Center, Bandung City. This research uses a descriptive method. The data collection instrument was a questionnaire with a sampling technique using purposive sampling. Data analysis used univariate analysis. The results of the research on the implementation of classes for pregnant women were mostly followed by pregnant women aged 20-35 years (75%), the most gestational age was 8 months (53.57%), high school education (39.28%), most of the respondents worked as a housewife (42.85%), and the implementation of the class for pregnant women is included in the good category (92.85%). The conclusion of the class program for pregnant women provides an opportunity for pregnant women to exchange information and learn from each other, so it is expected to be a continuously scheduled program as an optimization of mother's preparation for childbirth. Keywords: MMR, Pregnant Women Class, Implementation. ABSTRAK Program pembangunan kesehatan di Indonesia dewasa ini masih diprioritaskan pada upaya peningkatan derajat kesehatan Ibu dan anak, terutama pada kelompok yang paling rentan kesehatan yaitu ibu hamil, bersalin dan bayi pada masa perinatal. Keberhasilan program kesehatan ibu dapat dinilai melalui indikator utama Angka Kematian Ibu (AKI). Kelas Ibu Hamil merupakan sarana untuk belajar bersama tentang kesehatan bagi ibu hamil, dalam bentuk tatap muka dalam kelompok untuk meningkatkan pengetahuan dan keterampilan ibu-ibu mengenai kehamilan, persalinan, dan nifas. Tujuan penelitian ini untuk mengetahui pelaksanaan kelas ibu hamil di Wilayah Kerja UPTD Puskesmas Pasirkaliki Kota Bandung. Penelitian ini menggunakan metode deskriptif. Instrumen pengumpulan data adalah kuesioner dengan teknik pengambilan sampel menggunakan purposive sampling. Analisa data menggunakan analisis univariat. Hasil penelitian pelaksanaan kelas ibu hamil paling banyak diikuti oleh ibu hamil yang berusia 20- 35 tahun (75%), usia kehamilan paling banyak berusia 8 bulan (53,57%), pendidikan SMA (39,28%), sebagian besar responden bekerja sebagai Ibu Rumah Tangga (42,85 %), dan pelaksanaan kelas ibu hamil termasuk dalam kategori baik yaitu 92,85%. Kesimpulan program kelas ibu hamil memberikan kesempatan pada ibu hamil untuk saling bertukar informasin dan saling belajar satu sama lain, sehingga diharapkan menjadi program yang terus terjadwal sebagai optimalisasi persiapan ibu dalam persalinan. Kata Kunci: AKI, Kelas Ibu Hamil, Pelaksanaan.